Application of Simple Additive Weighting (SAW) for Best Decor at Mainaka Decoration - Anggi Melisa Nasution; William Ramdhan; Zulkarnain Sirait (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2026)
The rapid development of the event decoration service industry demands companies to be able to provide optimal services and meet client needs quickly and objectively. Mainaka Decoration as a company engaged in the field of event decoration services faces problems in the process of selecting the best decoration concept which is still done subjectively based on the designer's experience and intuition. This condition causes the decision-making process to be less effective, not standardized, and has the potential to cause a mismatch between client expectations and the decoration results provided. Therefore, a system is needed that is able to assist management in determining the best decoration concept based on measurable criteria. This study aims to design and build a Decision Support System (DSS) in selecting the best decoration concept by applying the Simple Additive Weighting (SAW) method. The SAW method is used to rank several alternative decoration concepts based on predetermined criteria, namely budget, aesthetics, work time, theme suitability, and durability of decoration materials. This study uses a quantitative method with data collection techniques through observation, interviews, and literature studies. The system is designed using Unified Modeling Language (UML) and implemented web-based using PHP programming language with MySQL database. The results of this study indicate that the application of the SAW method in the Decision Support System is able to provide recommendations for the best decoration concepts objectively and systematically according to client needs. The system built can help increase effectiveness and efficiency in the decision-making process, minimize subjectivity in assessing decoration alternatives, and improve service quality and customer satisfaction at Mainaka Decoration